2015
DOI: 10.1016/j.jcin.2014.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Remote Ischemic Conditioning Reduces Myocardial Infarct Size and Edema in Patients With ST-Segment Elevation Myocardial Infarction

Abstract: This randomized study demonstrated that in ST-segment elevation myocardial infarction patients treated by PPCI, RIC, initiated prior to PPCI, reduced MI size, increased myocardial salvage, and reduced myocardial edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
206
3
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(225 citation statements)
references
References 40 publications
5
206
3
7
Order By: Relevance
“…180 In patients with acute STsegment elevation myocardial infarction undergoing PCI, remote ischemic perconditioning with 4 cycles of 5-minute arm ischemia/5-minute reperfusion at hospital admission reduced both infarct size and edema on MRI. 181 Also in patients with acute myocardial infarction undergoing PCI, remote ischemic postconditioning by 3 cycles of lower limb ischemia/reperfusion reduced edema (MRI) and infarct size (MRI, biomarker), improved ST-segment resolution during reperfusion, but did not improve TIMI frame count or myocardial blush grading. 182 In the recent LIPSIA (from Leipzig) conditioning trial in patients undergoing primary PCI for acute ST-segment elevation myocardial infarction, postconditioning alone with 4 cycles of 30-second reocclusion/reperfusion failed to improve myocardial salvage and microvascular obstruction by MRI, but combined postconditioning with remote ischemic perconditioning by 3 cycles of 5-minute upper arm ischemia/5-minute reperfusion improved myocardial salvage, albeit reduced microvascular obstruction only nonsignificantly.…”
Section: Coronary Vascular Protection By Remote Ischemic Conditioningmentioning
confidence: 96%
“…180 In patients with acute STsegment elevation myocardial infarction undergoing PCI, remote ischemic perconditioning with 4 cycles of 5-minute arm ischemia/5-minute reperfusion at hospital admission reduced both infarct size and edema on MRI. 181 Also in patients with acute myocardial infarction undergoing PCI, remote ischemic postconditioning by 3 cycles of lower limb ischemia/reperfusion reduced edema (MRI) and infarct size (MRI, biomarker), improved ST-segment resolution during reperfusion, but did not improve TIMI frame count or myocardial blush grading. 182 In the recent LIPSIA (from Leipzig) conditioning trial in patients undergoing primary PCI for acute ST-segment elevation myocardial infarction, postconditioning alone with 4 cycles of 30-second reocclusion/reperfusion failed to improve myocardial salvage and microvascular obstruction by MRI, but combined postconditioning with remote ischemic perconditioning by 3 cycles of 5-minute upper arm ischemia/5-minute reperfusion improved myocardial salvage, albeit reduced microvascular obstruction only nonsignificantly.…”
Section: Coronary Vascular Protection By Remote Ischemic Conditioningmentioning
confidence: 96%
“…All studies that used an ischemic perconditioning protocol of repeated arm or leg ischemia/reperfusion in patients with acute STEMI found reduced infarct size, which was significant in most of them, no matter whether reperfusion was by primary PCI 96,[106][107][108][109][110][111] or thrombolysis 112 and no matter whether biomarker release or imaging was used to assess infarct size ( Figure 3). A retrospective analysis of the CONDI trial (Effect of Remote Ischemic Conditioning on Clinical Outcome in (Table 3).…”
Section: Remote Ischemic Conditioningmentioning
confidence: 99%
“…Remote ischemic conditioning by repetitive limb ischemia/reperfusion also reduces myocardial damage in patients undergoing elective interventional2 or surgical coronary revascularization3, 4, 5, 6 and in those with reperfused acute myocardial infarction 7, 8, 9, 10, 11, 12, 13. Cardioprotection was confirmed by reduced release of cardiac biomarkers2, 3, 4, 5, 6, 10 or by increased salvage in cardiac imaging7, 8, 9, 11 but also resulted in improved short‐5, 8 and more long‐term2, 4, 13, 14, 15 clinical outcome in retrospective analyses. Recently, the first prospective, randomized trial on patients with reperfused acute myocardial infarction confirmed improved clinical outcome as a primary end point of remote ischemic conditioning during follow‐up for 3.6 years 13.…”
Section: Introductionmentioning
confidence: 99%